ANALISIS KINERJA KEUANGAN PERUSAHAAN OTOMOTIF YANG LISTING DI BURSA EFEK INDONESIA (PADA 2011-2020) - Aldonna Putri Septiana; Muhammad Khadafi; Juwita Aprillia (Tinta Nusantara 2018 Vol.1, 2023)
The purpose of this study was to determine how big the level of profitability, solvency, liquidity, and activity ratios of automotive companies listed on the Indonesia Stock Exchange. Based on the analysis and discussion that has been carried out at PT Astra Internasional, Tbk and PT. Astra Otoparts, Tbk. So it can be concluded that PT Astra Internasional, Tbk and PT. Astra Otoparts, Tbk is a company that is included in the category of a healthy and good company because it is seen from the industry standards of its financial ratios, because it is almost able to reach the limits of its industry standards. even though the company is still able to cover the losses that occur even with a ratio of 1:1.